2020
DOI: 10.1111/clr.13601
|View full text |Cite
|
Sign up to set email alerts
|

Changes of clinical parameters at implants: A retrospective comparison of implants versus natural teeth over 5 years of supportive periodontal therapy

Abstract: ObjectivesTo compare clinical parameters of implants versus natural teeth over a period of 5 years during supportive periodontal therapy (SPT).Material and MethodsA total of 421 SPT patients were screened for implants (I) and corresponding control teeth (C). Data (patient level [P]: sex, age, smoking status, systemic diseases, adherence, oral hygiene indices, mean probing depth [PD]P, bleeding on probing [BOP]P, periodontal risk profile; implant/control tooth level [I/C]: PDI/C, BOPI/C; site level at implants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Consistently with our results, three recent studies [47][48][49] found that BOP exhibited less frequently in S despite higher values of plaque and PPD, however, these outcomes were not confirmed by a multivariate analysis. Moreover, three previous cross-sectional studies 26,27,50 supported the association that was found in the present study between BOP and PPD. Yet, in those reports smoking status failed to be significantly associated with BOP after controlling for potential confounders.…”
Section: Agreement and Disagreement With Previous Findingssupporting
confidence: 92%
“…Consistently with our results, three recent studies [47][48][49] found that BOP exhibited less frequently in S despite higher values of plaque and PPD, however, these outcomes were not confirmed by a multivariate analysis. Moreover, three previous cross-sectional studies 26,27,50 supported the association that was found in the present study between BOP and PPD. Yet, in those reports smoking status failed to be significantly associated with BOP after controlling for potential confounders.…”
Section: Agreement and Disagreement With Previous Findingssupporting
confidence: 92%
“…The placement of a dental implant involves one surgery moment, a prosthetic moment, and a step of periodic follow-up to assess the success and the maintaining of the ideal conditions of dental implants and patients’ tissues [ 18 ]. There are some factors that may influence the result of the treatment; some depend on the patient, such as the presence of systemic diseases (diabetes mellitus, diseases of coagulation, osteoporosis) [ 19 , 20 , 21 , 22 , 23 ], therapy with anticoagulants, bisphosphonates, cardio aspirin [ 24 ], physiology and anatomy of the treated structured (bone quantity available and density, mental nerve not far from the level of the bone crest) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; others depend on the operator (experience, methods, and instruments used, team skills) [ 33 ]. Nevertheless, we must consider that also in healthy patients and experienced operators, some implant complications (peri-implantitis, bone dehiscence, and impossibility to obtain ideal implant stability) may be a very common situation because of other etiologic agents, such as biomechanical factors or inadequate preparation of the site hosting the implant [ 19 , 24 , 25 , 26 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implant has no periodontal ligaments between the bone and the implant, and the bres are arranged in parallel, which cannot provide a physical barrier to bacterial invasion and limits the progression of periodontal disease 13 . Therefore, unlike natural teeth, implants are more vulnerable to in ltration by external substances or bacteria [15][16][17] . In addition, it is clinically di cult to determine whether cement remains in the subgingival region5 .…”
Section: Introductionmentioning
confidence: 99%